Soldiers and Victims: David Abrams’ Fobbit - M Alosman, M Ikbal (Dirasat: Human and Social Sciences, 2024)
Objectives: This paper aims to examine David Abrams’ Fobbit (2012) in terms of its approach to victimhood and the concept of war victims in the context of the Iraq War in 2003. Methods: The analysis is divided into two main constructs: ’American Victims,’ which examines the novel’s representation of American soldiers as victims of war and ’National Victims’ which explores the portrayal of Iraqis as war victims. The concept of victimhood is essential to the war narrative because it preserves the right for retribution to the afflicted and assigns responsibility to the other party for the violations. One side is absolved and becomes a victim, while the other is depicted as capable of committing terrible acts. Results: Despite the novel’s attempt to portray the suffering of Iraqis and describe some of the effects of the war on their lives, it also makes them responsible for most of their misery. American soldiers, though partially responsible for some major mistakes, emerge as the most prominent victims of the war in the novel. Conclusions: The study reveals how the image of American soldiers as victims of war dominates the narrative, erasing any presence of others as victims.